Kontribusi Self-Efficacy terhadap Stres Kerja pada Guru Ddi SLB Negeri 1 Harau - Auda Shufi Awalia; Zulmi Yusra (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to determine the contribution of self-efficacy to teachers' work stress at SLB Negeri 1 Harau, the only public special school in Harau District. Teachers at SLB face complex challenges in dealing with students with special needs, which has the potential to cause work stress. The study used a quantitative approach with a correlational method to test the relationship between self-efficacy and work stress. The research population is all teachers at SLB Negeri 1 Harau as many as 20 people, with a total sampling technique. The research instrument was in the form of a questionnaire on self-efficacy and work stress which was compiled based on the Likert scale. The results of the analysis showed a correlation value of 0.795** with df = 18 and r table = 0.443, which means that there is a significant and strong relationship between self-efficacy and work stress. The regression test using SPSS version 29 produced an Fcount of 21.974 > a Ftable of 3.28, so that H₀ was rejected and Hₐ was accepted. These findings show that self-efficacy contributes significantly to teachers' work stress. Teachers with high levels of self-efficacy tend to have better ability to manage work pressure and respond to learning challenges positively. This research provides important implications for the development of psychological intervention programs and self-efficacy improvement training for educators in an inclusive education environment.